The Role of Macroeconomics and Financial Performance in Shaping Stock Returns: Evidence From the Coal Industry on the Indonesia Stock Exchange - Ahmad Rizki Nurrahman; Subiakto Sukarno (Green Publisher Indonesia, 2025)
This study investigates the influence of macroeconomic variables and financial performance on stock returns in Indonesia’s coal industry over the period Q1 2015 to Q4 2024. Amid global uncertainty and the prolonged energy transition, coal remains a critical contributor to Indonesia’s economy and capital market. However, the sector faces increasing volatility and policy risk. Through panel data regression analysis, this study evaluates the effects of inflation, exchange rate, and coal price as macroeconomic indicators, along with financial performance variables including Gross Profit Margin (GPM), Return on Assets (ROA), Return on Equity (ROE), Current Ratio (CR), Debt to Asset Ratio (DAR), Debt to Equity Ratio (DER), Price to Book Value (PBV), and Price to Earnings Growth (PEG) on stock returns. The findings reveal that coal prices and financial performance indicators such as ROA, ROE, and PBV have a significant positive effect on stock returns, while inflation and exchange rate demonstrate mixed or insignificant impacts. The research confirms that strong internal performance and favorable external commodity conditions are key drivers of investor interest and stock valuation. This study provides valuable insights for investors, corporate managers, and policymakers in understanding the dynamics of the coal sector in Indonesia's capital market.